Immunogenicity and Safety of the Adjuvanted Recombinant Zoster Vaccine in Chronically Immunosuppressed Adults Following Renal Transplant: A Phase 3, Randomized Clinical Trial. (7th March 2019) - Vink, Peter; Ramon Torrell, Josep Maria; Sanchez Fructuoso, Ana; Kim, Sung-Joo; Kim, Sang-il; Zaltzman, Jeff; Ortiz, Fernanda; Campistol Plana, Josep Maria; Fernandez Rodriguez, Ana Maria; Rebollo Rodrigo, Henar; Campins Marti, Magda; Perez, Rafael; et al.
Abstract: Background: The incidence of herpes zoster is up to 9 times higher in immunosuppressed solid organ transplant recipients than in the general population. We investigated the immunogenicity and safety of an adjuvanted recombinant zoster vaccine (RZV) in renal transplant (RT) recipients ≥18 years of age receiving daily immunosuppressive therapy. Methods: In this phase 3, randomized (1:1), observer-blind, multicenter trial, RT recipients were enrolled and received 2 doses of RZV or placebo 1–2 months (M) apart 4–18M posttransplant. Anti–glycoprotein E (gE) antibody concentrations, gE-specific CD4 T-cell frequencies, and vaccine response rates were assessed at 1M post–dose 1, and 1M and 12M post–dose 2. Solicited and unsolicited adverse events (AEs) were recorded for 7 and 30 days after each dose, respectively. Solicited general symptoms and unsolicited AEs were also collected 7 days before first vaccination. Serious AEs (including biopsy-proven allograft rejections) and potential immune-mediated diseases (pIMDs) were recorded up to 12M post–dose 2. Results: Two hundred sixty-four participants (RZV: 132; placebo: 132) were enrolled between March 2014 and April 2017. gE-specific humoral and cell-mediated immune responses were higher in RZV than placebo recipients across postvaccination time points and persisted above prevaccination baseline 12M post–dose 2. Local AEs were reported more frequently by RZV than placebo recipients. Overall occurrences of renal function changes, rejections, unsolicited AEs, serious AEs, and pIMDs were similar between groups. Conclusions: RZV was immunogenic in chronically immunosuppressed RT recipients. Immunogenicity persisted through 12M postvaccination. No safety concerns arose. Clinical Trials Registration: NCT02058589. Abstract : The adjuvanted recombinant zoster vaccine was immunogenic in renal transplant recipients receiving daily immunosuppressive treatment. Humoral and cell-mediated immune responses persisted through 1 year postvaccination. Vaccination had no impact on renal function or rejection rate. No safety concerns arose.